2021
DOI: 10.1177/13524585211051059
|View full text |Cite
|
Sign up to set email alerts
|

Effects of voice rehabilitation in people with MS: A double-blinded long-term randomized controlled trial

Abstract: Background: Hypophonia is a prevailing problem in people with multiple sclerosis (PwMS). However, evidence supporting the effectiveness of voice rehabilitation is lacking. Objective: The aim of this study was to identify the most effective method to reduce hypophonia. Methods: In this randomized controlled trial, 44 PwMS were randomized to intensive and high-effort voice treatment groups, the LSVT-LOUD®, and conventional treatment group. Subjects received 16 treatments (4 sessions/week) lasting 45 minutes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…In the present prospective study, we collected data from a randomized controlled trial. 19 Forty-four consecutive inpatients were recruited from January 2018 to July 2019 at IRCCS Fondazione Don Carlo Gnocchi (Milan, Italy). Details of the study are provided elsewhere.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…In the present prospective study, we collected data from a randomized controlled trial. 19 Forty-four consecutive inpatients were recruited from January 2018 to July 2019 at IRCCS Fondazione Don Carlo Gnocchi (Milan, Italy). Details of the study are provided elsewhere.…”
Section: Samplementioning
confidence: 99%
“…Details of the study are provided elsewhere. 19 In brief, people with MS were randomized after completion of a baseline assessment using a randomization list and the following inclusion criteria: (1) a diagnosis of MS according to Thompson and McDonald criteria 20 ; (2) older than 18 years; (3) ability to understand the Italian language and the aims of the study; and 4) impairments in voice intensity during conversation (defined as a maximum voice intensity <60 dB SPL). 21 The exclusion criteria were: (1) the presence of other neurological disorders; (2) visual/hearing impairments that would hinder participation in the rehabilitation program;…”
Section: Samplementioning
confidence: 99%
“…A follow up study in this area with 24 patients, found improvements in speech loudness (SPL) and maximum phonation length, supported by improved respiratory function following a therapeutic singing intervention ( Tamplin et al, 2013 ). The Perceptual Voice Profile (PVP) and Voice Handicap Index (VHI), both are subjective rating scale, are used to assess vocal function scores ( Crispiatico et al, 2021 ). The results showed that CSCI patients had low voice quality, insufficient volume in long space, insufficient breath during speech, and common social disorder problems of varying degrees in social situations.…”
Section: Introductionmentioning
confidence: 99%